The Cambridge MRI database for animal models of Huntington disease - Sawiak, Stephen J.; Morton, A. Jennifer (NeuroImage (Orlando, Fla.), 2016)
We describe the Cambridge animal brain magnetic resonance imaging repository comprising 400 datasets to date from mouse models of Huntington disease. The data include raw images as well as segmented grey and white matter images with maps of cortical thickness. All images and phenotypic data for each subject are freely-available without restriction from (http://www.dspace.cam.ac.uk/handle/1810/243361/). Software and anatomical population templates optimised for animal brain analysis with MRI are also available from this site. •We describe our online database of Huntington's animal images.•400 images to date from mouse models (ex vivo R6/2 of various CAG lengths, YAC128)•12 images to date from sheep models (OVT73 in vivo)